The effect of entrepreneurial competencies on the performance of informal women micro-enterprise. - Nur Hakimah Mohd Suhaimi (2018)
It has been recognized that the information on the informal economic activities in Malaysia is still insufficient even though this sector plays a crucial role towards a developing country like Malaysia. This study is motivated by the entrepreneurial competencies in developing countries and how it affects the performance of informal women micro-enterprise.